From Olive Drupes to Olive Oil. An HPLC-Orbitrap-based Qualitative and Quantitative Exploration of Olive Key Metabolites - Kanakis, Periklis; Termentzi, Aikaterini; Michel, Thomas; Gikas, Evagelos; Halabalaki, Maria; Skaltsounis, Alexios-Leandros (Planta Medica, 2013)
The aim of the current study was the qualitative exploration and quantitative monitoring of key olive secondary metabolites in different production steps (drupes, paste, first and final oil) throughout a virgin olive oil production line. The Greek variety Koroneiki was selected as one of the most representative olives, which is rich in biological active compounds. For the first time, an HPLC-Orbitrap platform was employed for both qualitative and quantitative purposes. Fifty-two components belonging to phenyl alcohols, secoiridoids, flavonoids, triterpenes, and lactones were identified based on HRMS and HRMS/MS data. Nine biologically and chemically significant metabolites were quantitatively determined throughout the four production steps. Drupes and paste were found to be rich in several components, which are not present in the final oil. The current study discloses the chemical nature of different olive materials in a successive and integrated way and reveals new sources of high added value constituents of olives.
Keywords: olive oil production; olive drupes; HPLC-Orbitrap-HRMS/MS; oleocanthal; oleacein